FAKTOR RISIKO KEJADIAN IRITASI MATA PADA PENGGUNA KOLAM RENANG X DI KOTA SEMARANG - Bayu Wicaksono; Budiiyono Budiyono; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Chlorine is a disinfectant to kill pathogenic microorganisms in swimming pool. Residual chlorine in swimming pool can cause eye irritation. The purpose of this study was to determine the risk factors of eye irritation among swimmers in swimming pool X in Semarang. The type of research was observational analytic with cross-sectional design. The population in this study were all swimmers in swimming pool X and samples taken as many as 80 peoples with accidental sampling technique. Analysis used Chi Square with the level of error of 0.05. The results of this study showed that as many as 50% of respondents have got eye irritation. The average of residual chlorine as many as 4,26±2,433 mg/l, 85% swimmers not wear goggles and the average of swimming duration was 38,04±25,626 minutes. There was a significant association between the wear of goggles with the incidence of eye irritation in swimmers in Swimming Pool X (p-value = 0.002). While the variable levels of residual chlorine (p-value = 0.516) and the duration of the swim (p-value = 0.516) were no significant association with the incidence of eye irritation among swimmers in swimming pool X. The conclusion of this study was the swimmers who did not wear the goggles had eye irritation.